1975
DOI: 10.1044/jshd.4004.502
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Visual Feedback in Establishing Normal Vocal Intensity in Two Mildly Retarded Adults

Abstract: A voice-activated relay was used to provide visual feedback of vocal amplitude for two subjects who habitually used very soft voices. The relay system caused a light to go on when vocal intensity was 65 dB SPL or greater. Both subjects demonstrated significant increases in their use of normal vocal intensity. One subject was able to transfer this progress to spontaneous conversational settings. Though some difficulties in generalization and automatization were evident, this system is recommended for use with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As shown in Table II, only five studies (29.4%) mentioned long-term results. Whereas Andrews et al (1986), D'Antonio et al (1987 and Sime and Healey (1993) reported retention after respectively 3, 1 and 15 months, there was no longterm effect of biofeedback after 5 months (Brody et al, 1975), or, in one case, even in the second baseline period directly after biofeedback therapy (Till et al, 1987). Several advantages can be enumerated.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…As shown in Table II, only five studies (29.4%) mentioned long-term results. Whereas Andrews et al (1986), D'Antonio et al (1987 and Sime and Healey (1993) reported retention after respectively 3, 1 and 15 months, there was no longterm effect of biofeedback after 5 months (Brody et al, 1975), or, in one case, even in the second baseline period directly after biofeedback therapy (Till et al, 1987). Several advantages can be enumerated.…”
Section: Discussionmentioning
confidence: 95%
“…The biofeedback therapy in the participant described by Sime and Healey (1993) maintained the decreased laryngeal EMG levels at the 15-months follow-up. On the other hand, the two patients described in Brody et al (1975) showed no retention of the effects of biofeedback therapy after 5 months. Till et al (1987) reported that the therapeutic effect demonstrated in that study disappeared once the biofeedback stopped.…”
Section: Summary Of Tablesmentioning
confidence: 87%
See 3 more Smart Citations